2018
DOI: 10.1080/09546634.2018.1509046
|View full text |Cite
|
Sign up to set email alerts
|

Fractional carbon dioxide laser assisted delivery of topical tazarotene versus topical tioconazole in the treatment of onychomycosis

Abstract: Fractional CO laser-assisted drug delivery is an effective and safe treatment option for onychomycosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
12
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 19 publications
6
12
2
Order By: Relevance
“…The main clinical type of OM in this study was distrolateral subungual type then total dystrophic (TDO) and white superficial onychomycosis (WSO) which was similar to the study of Abd El‐Aal et al 8 who reported that DLSO was the predominant followed by TDO. Most patients in our study were with fingernail affection similar to the study of Abd El‐Aal et al 8 who reported that fingernails were more common than toenails being involved in 67% and 33% of patients, respectively. Toenails OM is more common than fingernails OM in Western studies 9 .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The main clinical type of OM in this study was distrolateral subungual type then total dystrophic (TDO) and white superficial onychomycosis (WSO) which was similar to the study of Abd El‐Aal et al 8 who reported that DLSO was the predominant followed by TDO. Most patients in our study were with fingernail affection similar to the study of Abd El‐Aal et al 8 who reported that fingernails were more common than toenails being involved in 67% and 33% of patients, respectively. Toenails OM is more common than fingernails OM in Western studies 9 .…”
Section: Discussionsupporting
confidence: 89%
“…Local treatment requires strong patient adherence because treatment time is generally long; moreover, OM‐related subungual hyperkeratosis is generally thick and this limits the penetration of the antimycotic drug 7 . The main clinical type of OM in this study was distrolateral subungual type then total dystrophic (TDO) and white superficial onychomycosis (WSO) which was similar to the study of Abd El‐Aal et al 8 who reported that DLSO was the predominant followed by TDO. Most patients in our study were with fingernail affection similar to the study of Abd El‐Aal et al 8 who reported that fingernails were more common than toenails being involved in 67% and 33% of patients, respectively.…”
Section: Discussionsupporting
confidence: 84%
“…A similar result had been reported in India by Wajid, Khaleel, & Begum Amirunnisa () who reported that Candida species was the most common isolates in 65 patients (43.3%) followed by NDM. Similar results were reported in a study from Egypt by Abd El‐Aal, Abdo, Ibrahim, & Eldestawy () who revealed that the commonest isolated fungi were yeast infection by 37% followed by NDMs infection by 22.5% and trichosporon species infection by 18% and dermatophyte infection was only detected in 10%. In contrast, other studies showed that the most common fungal isolate was dermatophyte (mainly Trichophyton rubrum ) followed by yeast (mainly Candida albicans ) (Kaur et al, ; Matos & Mariano, ).…”
Section: Discussionsupporting
confidence: 89%
“…To be effective, lasers should have a wavelength between 750 and 1300 nm to penetrate the nail, a pulse duration that is shorter than the “thermal relaxation time” of the fungus, and a spatially uniform beam that does not cause “hot spots” [ 6 , 107 ]. Several types of lasers have been used for the treatment of onychomycosis including long pulsed neodymium-doped yttrium aluminium garnet (Nd:YAG) laser, diode laser, and fractional carbon dioxide (CO 2 ) laser [ 118 - 129 ]. Studies have shown that laser therapies are somewhat effective in achieving cosmetic endpoints in onychomycosis, but do not exceed or equal the efficacy of current topical and oral antifungal therapies in terms of achieving medical endpoints [ 39 , 130 ].…”
Section: Treatmentmentioning
confidence: 99%